Asian sand dust exacerbates airway inflammation in a mouse model of asthma - Se-Jin Lee; So-Won Pak; Woong-Il Kim; Sin-Hyang Park; Young-Kwon Cho; Tae-Won Kim; Je-Won Ko; Joong-Sun Kim; Jong-Choon Kim; In-Hyeon Kim; Sung-Hwan Kim; In-Sik Shin (Laboratory Animal Research)
Abstract Background Asian sand dust (ASD), generated from the deserts of China and Mongolia, mainly affects the human health of several countries in Northeast Asia including China, Korea, and Japan. In this study, we investigated the toxic effects of ASD on respiratory tract and explored the effects of ASD exposure on allergic asthma using ovalbumin-induced asthma model. C57BL/6 male mice were used for both the toxicity and allergic asthma studies. ASD (10, 20, and 40 mg/kg) was administered intranasally on days 1, 3, and 5. For allergic asthma, mice were sensitized with OVA (20 µg/mouse) and aluminum hydroxide (2 mg) on days 1 and 15, followed by OVA inhalation (1%, w/v) on days 22, 24, and 26, with subsequent ASD instillation on days 21, 23, and 25. Results ASD exposure showed the elevation of respiratory inflammation including inflammatory cell infiltration, cytokine production, and mucus secretion with the increase in phosphorylated (p)-nuclear factor-kappa B (NF-κB) p65 expression. In addition, ASD exposure to asthma model significantly increased airway responsiveness, inflammatory cell count and mucus secretion with the elevation of cytokines and immunoglobulin E, which were accompanied with the increases in p-NF-κB p65, p-p38 and cyclooxygenase 2 (COX2). Conclusions Therefore, ASD exposure induces respiratory inflammation and aggravates the progression of allergic asthma, which was closely associated with the phosphorylation of NF-κB. Respiratory exposure to ASD causes inflammation, upregulation of cytokines, p-NF-κB, and COX2, which can exacerbate asthma.